Jurisdictions of International Commercial Arbitration in Afghanistan and UNCITRAL Laws - Fallah, Eid Mohammad (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
One of the important issues in international commercial arbitration is the arbitration board, which consists of one or more arbitrators to resolve commercial disputes based on the agreement of the parties to the dispute, or by the arbitration organization or the court, and is dissolved after dealing with the commercial disputes. In this research we examine the competence of the arbitration board in international commercial arbitration, focusing on its ability to make decisions regarding jurisdiction and the examination of the existence of the arbitration agreement. The research employs a descriptive-analytical method and relies on library and electronic sources for data collection. The findings designate that the arbitration board, per the Afghanistan Arbitration Law and the UNCITRAl Model Law on International Commercial Arbitration, has the authority to determine its jurisdiction and observe the existence of the arbitration agreement. It is established that the principle of competence-competence is widely accepted by the laws of many countries. However, it is elucidated that the subject matter jurisdiction lies with the agreement of the parties involved. The research highlights the importance of the arbitration board in impartially resolving commercial disputes evolving from economic and commercial contracts and emphasizes its role in achieving quick and fair dispute resolution.